2014
DOI: 10.1371/journal.pone.0091815
|View full text |Cite
|
Sign up to set email alerts
|

The Focal Adhesion-Localized CdGAP Regulates Matrix Rigidity Sensing and Durotaxis

Abstract: Motile cells are capable of sensing the stiffness of the surrounding extracellular matrix through integrin-mediated focal adhesions and migrate towards regions of higher rigidity in a process known as durotaxis. Durotaxis plays an important role in normal development and disease progression, including tumor invasion and metastasis. However, the signaling mechanisms underlying focal adhesion-mediated rigidity sensing and durotaxis are poorly understood. Utilizing matrix-coated polydimethylsiloxane gels to manip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
61
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 70 publications
5
61
0
Order By: Relevance
“…23,24 The molecular connections between focal adhesions, cytoskeletal filaments and nuclear scaffolds may produce integrated changes in cellular and nuclear structure. 20,21,25 It has been shown that the differentiation of murine MSCs into a chondrocytic phenotype required a rounded cell shape.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 The molecular connections between focal adhesions, cytoskeletal filaments and nuclear scaffolds may produce integrated changes in cellular and nuclear structure. 20,21,25 It has been shown that the differentiation of murine MSCs into a chondrocytic phenotype required a rounded cell shape.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, CdGAP (Cdc42 GTPase-activating protein)/ARHGAP31, a GAP for Rac1 and Cdc422526, was reported to be highly expressed in human umbilical vein endothelial cells (HUVECs)24, and to be regulated in Zebrafish by the transcription factor Ets, a master regulator of angiogenesis2728. Outside of the vascular system, pro-migratory and pro-invasive functions were ascribed to CdGAP, which was shown to regulate directional membrane protrusions of migrating osteosarcoma cells293031 and TGFβ-dependent cell motility and invasion of breast cancer cells32. Recently, truncating mutations in the terminal exon of the CdGAP gene were identified in patients with a rare developmental disorder, Adams-Oliver Syndrome (AOS)3334, which is frequently associated with cardiac and vascular anomalies3536.…”
mentioning
confidence: 99%
“…Importantly, unlike polyacrylamide substrates, the ECM components do not have to be chemically cross-linked to PDMS. Indeed, the fibronectin coating is approximately equivalent on both the PDMS and the glass surfaces, as determined by staining with an antibody specific to fibronectin 11 . Since previous studies have shown that cells behave the same on either PDMS or polyacrylamide substrates, the use of PDMS substrates provides a much easier model with which to study mechanotransduction in cells 10,12 .…”
Section: Discussionmentioning
confidence: 99%
“…We have recently used this assay to study how the focal adhesion signaling protein cdGAP regulates mechanosensing and durotaxis 11 . Clearly, there are numerous cellular components in addition to focal adhesions, such as cytoskeletal elements, protein trafficking components and ion channels that are involved in mechanical signaling and thus may also contribute to the regulation of durotaxis [13][14][15] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation